Filamin A is reduced and contributes to the CASR sensitivity in human parathyroid tumors. (February 2017) - Mingione, Alessandra; Verdelli, Chiara; Ferrero, Stefano; Vaira, Valentina; Guarnieri, Vito; Scillitani, Alfredo; Vicentini, Leonardo; Balza, Gianni; Beretta, Edoardo; Terranegra, Annalisa; Vezzoli, Giuseppe; Soldati, Laura; et al.
Abstract : Parathyroid tumors display reduced sensitivity to extracellular calcium ([Ca 2+ ]o ). [Ca 2+ ]o activates calcium-sensing receptor (CASR), which interacts with the scaffold protein filamin A (FLNA). The study aimed to investigate: (1) the FLNA expression in human parathyroid tumors, (2) its effects on the CASR mRNA and protein expression, and (3) on ERK signaling activation, (4) the effect of the carboxy-terminal CASR variants and (5) of the treatment with the CASR agonist R568 on FLNA-mediated ERK phosphorylation in HEK293 cells. Full-length FLNA immunostaining was variably reduced in parathyroid tumors. Immunofluorescence showed that FLNA localized in membrane and cytoplasm and co-localized with CASR in parathyroid adenomas (PAds)-derived cells. Cleaved C-terminus FLNA fragment could also be detected in PAds nuclear protein fractions. In HEK293 cells transfected with 990R-CASR or 990G-CASR variants, silencing of endogenous FLNA reduced CASR mRNA levels and total and membrane-associated CASR proteins. In agreement, FLNA mRNA levels positively correlated with CASR expression in a series of 74 PAds; however, any significant correlation with primary hyperparathyroidism severity could be detected and FLNA transcript levels did not differ between PAds harboring 990R or 990G CASR variants. R568 treatment was efficient in restoring 990R-CASR and 990G-CASR sensitivity to [Ca 2+ ]o in the absence of FLNA. In conclusion, FLNA is downregulated in parathyroid tumors and parallels the CASR expression levels. Loss of FLNA reduces CASR mRNA and protein expression levels and the CASR-induced ERK phosphorylation. FLNA is involved in receptor expression, membrane localization and ERK signaling activation of both 990R and 990G CASR variants.